Penerapan Problem Based Learning Terpadu Paradigma Konstruktivisme Vygotsky Pada Kurikulum Merdeka Belajar - Setiyaningsih, Suci; Subrata, Heru (Jurnal Ilmiah Mandala Education (JIME), 2023)
The phenomenon of the problem that could seen in general was how the learning continues to run effectively as learning in the classroom. The arise of discourse and studies on constructivist learning approaches were usually more directed at what and how learning with Vygotsky’s constructivism paradigm had applied. In this regard, it was necessary to apply a significant Independent Learning Curriculum in providing free and comfortable learning opportunities for students to learn calmly, relaxed and happily without stress and pressured by paying attention to their natural talents, without forcing them to study or master a field of knowledge. beyond their hobbies and abilities. The study of what learning with Vygotsky’s constructivism paradigm was usually done by contrasting the constructivist learning approach with other learning approaches (behavioristic). This study aimed to identify the application of project-based learning integrated with Vygotsky's constructivism paradigm in the Independent Learning Curriculum in Elementary Schools. The approach in this journal uses a qualitative approach combined with a literature study method. The results of the study concluded that there were more concrete and valid steps for setting students to implement project-based learning which was integrated with Vygotsky's constructivism paradigm in supporting the Independent Learning Curriculum as follows: 1.) Preparing introduction and problem formulations; 2.) Integration in designing, forming groups, gathering information: brief presentations, problem-solving, collaborative processes between students and teachers, as well as students' independence in completing projects; 3.) Conduct evaluations, by interpreting and making comparisons, concluding & making project reports.